The Epistemic Basis for Political Opposition: Rejoinder to Min. Issue 3 (1st October 2016) - Muirhead, Russell
ABSTRACT: As Min argues, any defense of democracy must include an epistemic element. But this does not mean that the will of the majority always tends to be right. It means only that we cannot identify in advance a minority that is likelier to get it right than everyone else. This fact is consistent with the possibility, even the likelihood, that the majority will more often be wrong than right. Those who find themselves in the minority should not be cowed into submission by the overall epistemic advantage of democracy: in any given case, a dissenter from the majority view may be right. Likewise, institutions such as parties are crucial in allowing minorities—and majorities—to persevere. Not only parties, but practices of dissent and opposition more broadly, are inseparable from the epistemic case for democracy.